Respuesta :

Answer:

Step-by-step explanation:

When we use the distributive property for expanding polynomial products, we often use it in the form ...

  (a +b)c = ac +bc

Here, we have ...

  (a +b) = (x -1)   ⇒   a=x, b=-1

  c = (4x+2)

So, the proper application of the distributive property looks like ...

  (a +b)c = ac +bc

  (x -1)(4x +2) = x(4x+2) -1(4x+2) . . . . . different from the work shown

We must conclude ...

  The distributive property was not applied correctly in the first step.

ACCESS MORE